On the interpretation of the enthalpy of solvation of hydroxyl cyclohexane derivatives in different solvents - Costa, Felisbela S. (2000)
Scaled particle theory was used for calculating the enthalpy of cavity formation in the solvation process of hydroxyl cyclohexane derivatives in water and in organic solvents. From the values calculated for the enthalpy of formation of the cavity and from those quoted for the enthalpy of solvation, the enthalpy of solute/solvent interaction was determined. This thermodynamic property shows that the formation of a cavity is an important contribution to the enthalpy of solvation, and is strongly dependent on the structure of the solvent. Unexpected results observed for water as compared with organic solvents are due to the differences in the cavity formation term rather than to solute/solvent interactions.